Development of the Japanese Version of the Leeds Assessment of the Neuropathic Symptoms and Signs Pain Scale: Diagnostic Utility in a Clinical Setting. Issue 6 (1st December 2016) - Isomura, Tatsuya; Sumitani, Masahiko; Matsudaira, Ko; Kawaguchi, Mika; Inoue, Reo; Hozumi, Jun; Tanaka, Takeyuki; Oshima, Hirofumi; Mori, Kanto; Taketomi, Shuji; Inui, Hiroshi; Tahara, Keitaro; et al.
Abstract: Objective: We aimed to assess the diagnostic utility of the linguistically validated Japanese version of the Leeds Assessment of Neuropathic Symptoms and Signs Pain Scale (LANSS‐J) as a screening tool for neuropathic pain in the clinical setting. Methods: Patients with neuropathic pain or nociceptive pain who were 20 to 85 years of age were included. Sensitivity and specificity using the original cutoff value of 12 were assessed to evaluate the diagnostic utility of the LANSS‐J. Sensitivity and specificity with possible cutoff values were calculated, along with area under the receiver operating characteristic curve. We then evaluated agreement regarding assessment of the LANSS‐J by two investigators. We used the intraclass correlation coefficient (ICC) for the total score and Cohen's kappa coefficient for each item. Results: Data for patients with neuropathic pain ( n = 30) and those with nociceptive pain ( n = 29) were analyzed. With a cutoff of 12, the sensitivity was 63.3% (19/30) and the specificity 93.1% (27/29). Sensitivity improved substantially with a cutoff of ≤ 11 (≥ 83.3%, 25/30). High specificity (93.1%, 27/29) was sustained with a cutoff of 9 to 12. The ICC for the total score was 0.85, indicating sufficient agreement. Kappa coefficients ranged from 0.68 to 0.84. Conclusions: The LANSS‐J is a valid screening tool for detecting neuropathic pain. Our results suggest that employing the original cutoff value provides high specificity, although a lower cutoff value of 10 or 11 (with its high specificity maintained) may be more beneficial when pain attributed to neuropathic mechanisms is suspected in Japanese patients.